Studying the Requirements of International Human Rights Regarding the Right to Education of Migrant Children - Mahya Saffarinia (فقه و حقوق خانواده)
AbstractChildren are among the most vulnerable human groups, that it is necessary to provide specific support in accordance with international human rights standards to ensure their growth and development. Among all children, certain individuals are more susceptible to vulnerability due to specific circumstances. Migrant children and all related subcategories, including displaced children, homeless children, refugees, asylum seekers and stateless children are considered among the most vulnerable groups. International human rights standards have articulated various provisions for safeguarding the rights of these groups in various dimensions of life. This study focuses on the examination of the details of the right to education of these children, elucidating the relevant legal requirements that governments and other stakeholders worldwide must be adhered. In line with this focus, studying the general commitments of countries in the field of the right to education has also been conducted. The outcome of this study emphasizes that no country is without its challenges in this regard and introduces the international legal requirements concerning the right to education of the studied group of children. This analysis can be particularly beneficial for policymakers, governmental executives, and non-governmental organizations in our country, which hosts hundreds of thousands of immigrants. Relevant explanations regarding Iran's legal system have also been presented within the main discourse to further facilitate the realization of this important matter.This study focuses on the examination of the right to education for these children, elucidating the relevant legal requirements that governments and other stakeholders worldwide must adhere to. In line with this focus, a review of the general commitments of countries in the field of the right to education has also been conducted. The approach of this review emphasizes that no country is without its challenges in this regard and introduces the international legal requirements concerning the right to education for the studied group of children. This analysis can be particularly beneficial for policymakers, governmental executives, and non-governmental organizations in our country, which hosts hundreds of thousands of immigrants. Relevant explanations regarding Iran's legal system have also been presented within the main discourse to further facilitate the realization of this important matter.